The Caatinga biome and ‘the unbearable lightness of being’: A conservationist approach with high school students using cordel literature (Research, Society and Development, 2024)
Of the five biomes present in Brazilian territory, the Caatinga is undoubtedly the one that faces the most problems. Currently, this ecosystem has undergone an accelerated process of desertification due to human activity. Therefore, there is a need to discuss this biome not only from an ecological point of view, but also from a social perspective. On the other hand, the construction of knowledge occurs through different paths, including the fusion of science and art. In this context, cordel literature stands out as a potential pedagogical instrument. In this sense, the objective of this article was to present the results of a social research on the theme of the Caatinga Biome with high school students, in which cordel literature was used. For this purpose, dialogued classes were held with shared readings based on the cordel entitled: The Caatinga Biome and ‘the sustainable lightness of being’. After approaching the topic, participants were invited to evaluate the proposed activity. Participants evaluated everything from the topic to the mediator's approach. Analysis of the results showed that there was good acceptance by participants regarding the proposed methodology. At the end of the activity, the work was evaluated as Good (22-35%), Very Good (25-40%) and Excellent (25-60%) by the majority of participants. This demonstrated that there was good acceptance by the participants regarding the proposed methodology. Furthermore, the work helped to awaken in students a greater awareness and appreciation of their biome.